Polysulfide: Sorbent made from waste cooking palm oil for petroleum refinery wastewater - Jun Haslinda, Shariffuddin; Mohd Faizal, Ali; Nayeem, Abdullah (2021)
Refinery industries produces almost 1.6 times wastewater compared to the petroleum products. Heavy metals and oily compounds are considered as most dangerous pollutants. Adsorption is the easiest and most effective method to treat the refinery wastewater. Polysulfides are cost effective and easy to produce in industrial scale. Waste cooking palm oil is the crosslinking monomer of polysulfide. It is abundant and itself hazardous. Elemental sulfur which is a by-product is abundant as well.